Analysis of colonization factor antigen I, an adhesin of enterotoxigenic Escherichia coli O78:H11: fimbrial morphology and location of the receptor-binding site. - Bühler, T (1991)
Colonization factor antigen I (CFA/I) of enterotoxigenic Escherichia coli was dissociated into one type of subunit (15 kDa). The dissociation was achieved either by heating CFA/I in sodium dodecyl sulfate at 100 degrees C or by heating it for 20 min in water. Heating in water to 100 degrees C yielded only in the 15-kDa subunit, but heating to 85 degree C yielded small amounts of oligomers in addition. The monomeric subunits obtained after heating in water are stable, as demonstrated by gel permeation chromatography and sodium dodecyl sulfate-polyacrylamide gel electrophoresis without heating prior to the electrophoretic run. These subunits inhibited CFA/I-induced hemagglutination, indicating that they had maintained their receptor-binding properties. When the hybridoma technique was used, two types of monoclonal anti-CFA/I antibodies were obtained. Antibodies obtained by immunization with the purified subunits were more reactive with subunits than with fimbriae, as shown by enzyme-linked immunosorbent assay. These antibodies strongly inhibited CFA/I-induced hemagglutination. When examined by immunoelectron microscopy, these antibodies seemed to label the fimbrial tips. A similar labeling pattern was obtained with gold particles modified with the receptor ganglioside GM2. Antibodies obtained by immunization with fimbriae reacted in enzyme-linked immunosorbent assays equally well with fimbriae and subunits. They inhibited CFA/I-induced hemagglutination only slightly. Immunoelectron microscopy revealed that these antibodies labeled the fimbriae densely and regularly over their entire lengths. In a coagglutination experiment with Staphylococcus aureus and monoclonal antibodies, the subunits retained their receptor-binding properties. From these results, we conclude that CFA/I fimbriae consist entirely of one type of adhesive subunit, of which only the one at the tip is accessible to the receptor.